The psychopathological profile of the abused woman: projective - behtan, abd elkader (Journal of Social Sciences and Humanities, 2021)
Violence in all its senses and in all cases, physical or verbal, can cause a physical or moral injury to a woman, because of the exercise of force, of coercion, or indifference, intentionally or not, but it can reach the level of extreme violence, such as rape, or those behaviors of the closest people, such as the husband or others. It can cause this violent aggression a traumatics pains. Because this abuse of the victim in such factors, individually or in combination, will result in a fragility of the narcissism of the woman and thus an imbalance of her personality. In our projective psychological study, we question the nature of the psychopathological profile of a beaten woman. In particular, a 36-year-old disabled mother in a rural area of wilaya of Guelma who was raped several times, gave birth to illegitimate children and received no medico-psychological-social care. We will try to detect her psychic functioning using the Rorschach test. The findings showed that the subject is in a traumatic state, caused by rape, her basal narcissism is fragile, seems to be mentally retarded, an unsatisfactory rationality and a disturbance of the level of thought.